Utilization of the Teacher-Made Strategic Intervention Material with Google Classroom in Improving the Performance of the Challenged Learn-ers - Cacay, Abraham (Future Science / FSH-PH Publications, 2021)
This classroom-based action research aimed to improve the performance of the challenged learners in Physical Science. The combination of Strategic Intervention Material (SIM) with the aid of Google Classroom was employed as an innovation to help the respondents master the competency-based skills that they were not developed during regular classroom teaching. In a combination of qualitative and quantitative designs, this research employed observation and participation, survey, and content-based assessment as data-gathering instruments. There were 40 identified challenged learners selected purposively (10 students for each of the four sections) based on their achievement scores after the long quiz, who took part in the study. The quantitative data were processed through Statistical Package for Social Sciences (SPSS), while the obtained qualitative data were interpreted using the phenomenological methodology. Results revealed an increase in the performance level of the challenged learners based on the increase of the mean percentage score of the posttest. Additionally, it showed that SIM promotes learning retention based on their scores in the delayed-posttest, and Google classroom motivates their learning intention towards the subject, Physical Science.